(untitled) (Dhaka University Journal of Business Studies, 2021)
Academic finance research is largely overshadowed by functionalist paradigm, and this limit positive contribution to knowledge. Hence, finance literature faces criticism, which highlights the justification of having a diversified philosophical stance. By investigating contemporary papers on investment benchmarks, sustainable finance and behavioural finance, we identify that modern finance researchers are rethinking about the research paradigm to bring paradigmatic diversification rather than being stagnant to positivism. Journal of Business Studies, Vol. XLII, No. 1, April 2021 Page 59-72